Crystal structure of the Legionella pneumophila Lpg2936 in complex with the cofactor S‐adenosyl‐L‐methionine reveals novel insights into the mechanism of RsmE family methyltransferases. (27th October 2017) - Pinotsis, Nikos; Waksman, Gabriel
Abstract: The methylation of U1498 located in the 16S ribosomal RNA of Escherichia coli is an important modification affecting ribosomal activity. RsmE methyltransferases methylate specifically this position in a mechanism that requires an S‐adenosyl‐L‐methionine (AdoMet) molecule as cofactor. Here we report the structure of Apo and AdoMet‐bound Lpg2936 from Legionella pneumophila at 1.5 and 2.3 Å, respectively. The protein comprises an N‐terminal PUA domain and a C‐terminal SPOUT domain. The latter is responsible for protein dimerization and cofactor binding. Comparison with similar structures suggests that Lpg2936 is an RsmE‐like enzyme that can target the equivalent of U1498 in the L. pneumophila ribosomal RNA, thereby potentially enhancing ribosomal activity during infection‐mediated effector production. The multiple copies of the enzyme found in both structures reveal a flexible conformation of the bound AdoMet ligand. Isothermal titration calorimetry measurements suggest an asymmetric two site binding mode. Our results therefore also provide unprecedented insights into AdoMet/RsmE interaction, furthering our understanding of the RsmE catalytic mechanism. Abstract : PDB Code(s):5O95 ;5O96